IMPLEMENTASI PEMBATASAN USIA NIKAH PASAL 07 UU NO 16 TAHUN 2019 SEBAGAI UPAYA PEMERINTAH DALAM MEMINIMALISIR PERNIKAHAN DINI: Studi Kasus di Kantor Urusan Agama Kecamatan Tlogosari Kabupaten Bondowoso - Soviah, Amrotus; Rofiki (Program Studi Hukum Keluarga Islam, 2022)
The practice of underage marriage has become a culture among the community. This is a problem that never ends. One of the Government's efforts to minimize the practice of underage marriage is to implement ARTICLE 07 of Law No. 16/2019 concerning restrictions on the age of marriage. This study focuses on the application of marriage age restrictions Article 7 of Law Number 16 of 2019 on early marriage and analyzes and describes the supporters and obstacles to the application of marriage age restrictions in early marriage at the Tlogosari District Religious Affairs Office. This research used a qualitative descriptive method and took place at the Religious Affairs Office, Tlogosari District, Bondowoso Regency. The research informants were the Head of the KUA, the Village Head, and the community involved in the implementation of marriage age restrictions. The results of this study indicate that the implementation carried out is guidance in the form of socialization to the community in villages and at the KUA. The success of the implementation is assessed by the rate of decline in underage marriage practices in 2020 and 2021. The social and cultural conditions of the community are one of the obstacles to the implementation of restrictions on the age of marriage because this context has a major influence on the mindset and lifestyle of the community which is difficult to change directly. So that until now there is still the practice of underage marriage Translated with www.DeepL.com/Translator (free version)